2023
DOI: 10.1002/rcr2.1155
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1‐negative non‐small cell lung cancer harbouring a rare BRAF mutation with successful treatment of first‐line pembrolizumab plus chemotherapy: A case report and review the literature

Abstract: BRAF mutations are uncommon in non‐small cell lung cancer (NSCLC), accounting for less than 5% of all NSCLC cases. The utilization of targeted therapies in non‐V600E BRAF mutant NSCLC is considered controversial, although non‐V600E genotype is reported in ~50% of all BRAF mutant patients. We document the case of a 63‐year‐old patient with NSCLC harbouring a rare BRAF E501Q mutation, who had prolonged response to immunotherapy combined with chemotherapy in Vietnam. The patient was diagnosed with metastatic PD‐L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A population of 37 patients with non V600E BRAF -mutant NSCLC, reported by Murciano-Goroff et al, treated with ICI, showed an ORR of 26% ( 29 ). A case of NSCLC harboring a rare BRAF E501Q mutation and PD-L1 negative expression reported a durable response after first-line treatment with ICIs and pemetrexed; the patient was alive 38 months after treatment initiation ( 30 ). Rittberg et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A population of 37 patients with non V600E BRAF -mutant NSCLC, reported by Murciano-Goroff et al, treated with ICI, showed an ORR of 26% ( 29 ). A case of NSCLC harboring a rare BRAF E501Q mutation and PD-L1 negative expression reported a durable response after first-line treatment with ICIs and pemetrexed; the patient was alive 38 months after treatment initiation ( 30 ). Rittberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…A population of 37 patients with non V600E BRAF-mutant NSCLC, reported by Murciano-Goroff et al, treated with ICI, showed an ORR of 26% (29). A case of NSCLC harboring a rare BRAF E501Q mutation and PD-L1 negative expression reported a durable response after first-line treatment with ICIs and pemetrexed; the patient was alive 38 months after treatment initiation (30). Rittberg et al demonstrated prolonged disease control over 4 years with ICI monotherapy in a 61-year-old patient with advanced NSCLC harboring the BRAF G469A mutation and PD-L1 expression >50% (31).…”
Section: Discussionmentioning
confidence: 99%